Articulation of the Archipelago's Islamic Education-al Thought - Babun Suharto; Fariza Md Sham; Erma Fatmawati; Shoni Rahmatullah Amrozi (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2023)
The difference between the intellectual tradition of the pesantren and other forms of education is the existence of the sanad. From the perspective of Ibn Qayyim Al-Jauzy, sanad can be said to go beyond thecologicalal linearity of Islamic knowledge which is commonly called ‘ilm jally. Not only that, Imam Syafi'i once said that if knowledge is not memorized by the sanad in the book then the Zindiq people will preach in the pulpit. The famous saying of Imam Abdullah bin Mubarak says, and is part of religion, without sanad surely people will say whatever they want. Even advanced sanad (ittishal al-sanad) is one of the conditions for the validity of a hadith as described in the musthalahul hadith book. For this reason, hadith expert scholars (al-muhadditsin) pay great attention to sanad in their disciplines. Most of this muhadditsin write special books about sanad. In its development, not only about the study of hadith, all scientific enthusiasts, book history, and scientific genealogy through teachers and students are written in a book known as tsabat. In the context of scientific knowledge, it can then be traced to the products of his thought. For this reason, the author wants to provide a re-description, of how true the thinking of native Indonesian (archipelagic) scholars is in the context of building an existing national attitude